Morning bliss / Noraziah Mohd Amin - Mohd Amin, Noraziah (Academy of Language Studies, 2022)
The sun smiled shiningly above the sky. Spreading its rays, the moist mist must leave. White clouds walked with the wind and passed by. Creepy-crawlies crept and crawled till eve.